World Flutelore : Folktales, Myths, and Other Stories of Magical Flute Power - Olsen, Dale A. (Dale Alan) (Book collections on Project MUSE., 2013)
"In many places around the world, flutes and the sounds of flutes are powerful magical forces for seduction and love, protection, vegetal and human fertility, birth and death, and other aspects of human and non-human behaviour. This book explores the cultural significance of flutes, flute playing, and flute players from around the world as interpreted from folktales, myths, and other stories - in a word, 'flutelore'."--